Using the Internet for Informal Learning about Joining the Brain Drain: A Qualitative Central/East European and Pacific Perspective - Roger Boshier (Adult Education Research Conference, 2002)
The Internet greatly expedites the process of “shooting through” from one’s home country. An online survey of Slovaks, New Zealanders and others suggests the Internet expedites leaving home – largely because of its informality and the way it erodes official control.